The Living and Working Together Perspective on Creativity in Organizations - Gazzaroli, Diletta; Gozzoli, Caterina; Sánchez-Gardey, Gonzalo (Frontiers in Psychology, 2019)
Although creativity represent a cornerstone for organizations that want to keep up with competitors, customers and the current socio-economic context, there is a dearth in the literature of systemic and comprehensive models focused on the complexity and addressing several dimensions and factors. In this context,, we propose the perspective of “Working and Living Together in Organizations” to enrich the scientific dialogue with a proposition that aims to hold together different variables of interaction and relationship between different parts of the organization (Gozzoli, 2016a, 2016b). In fact, according to our previous studies (Frascaroli, Gozzoli, & D'Angelo, 2016; Gorli, Ripamonti, & Galuppo, 2016; Marta et al., 2016; Saita et al., 2016; Tamanza, Gozzoli, & Gennari, 2016), a generative living and working together environment is itself directly linked to creativity and innovative processes. This is because in a generative living and working together environment relationality—that is, the possibility of exchange among workers mediated by the object of work—is enabled. With this study, we intend to provide a contribution to the creativity study field, applying our perspective to an extensive level of analysis. The model was tested using the Exploratory Structural Equation Modelling methodology with EQS-6.3. Our results found some interesting elements in support of the theory behind this study.